Strategic Management Practices of School Principals in Enhancing Teacher Performance in Early Childhood Education Institutions - Laili Fitriyah; Suyanto Suyanto; M. Furqon Wahyudi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aimed to describe the strategic management practices implemented by school principals in enhancing teacher performance in Early Childhood Education (ECE) institutions, particularly at TK Negeri Pembina Bangil. The study was motivated by the crucial role of school principals as instructional leaders in creating a conducive working environment and fostering teachers’ professional growth and performance. A qualitative approach with a case study design was employed. Data were collected through observations, in-depth interviews, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, which consists of data reduction, data display, and conclusion drawing. The findings revealed that the principal performed multiple roles as an instructional leader, resource manager, supervisor, motivator, and facilitator in improving teacher performance. Several strategic practices were implemented, including continuous professional development, clinical supervision, the establishment of a collaborative culture, the integration of educational technology, and the provision of rewards and recognition for outstanding performance. These strategies positively contributed to improving teachers’ pedagogical and professional competencies, work motivation, instructional quality, job satisfaction, and children's developmental outcomes. The study concludes that sustainable strategic management practices implemented by school principals play a significant role in strengthening teacher performance and enhancing the overall quality of early childhood education.